A randomized controlled trial of pre-procedure simethicone and N-acetylcysteine to improve mucosal visibility during gastroscopy – NICEVIS - Basford, Peter John; Brown, James; Gadeke, Lisa; Fogg, Carole; Haysom-Newport, Ben; Ogollah, Reuben; Bhattacharyya, Rupam; Longcroft-Wheaton, Gaius; Thursby-Pelham, Fergus; Neale, James R.; Bhandari, Pradeep (Endoscopy International Open, 2016)
Background and study aims: Mucosal views can be impaired by residual bubbles and mucus during gastroscopy. This study aimed to determine whether a pre-gastroscopy drink containing simethicone and N-acetylcysteine improves mucosal visualisation.Patients and methods: We conducted a randomized controlled trial recruiting 126 subjects undergoing routine gastroscopy. Subjects were randomized 1:1:1 to receive: A—pre-procedure drink of water, simethicone and N-acetylcysteine (NAC); B—water alone; or C—no preparation. Study endoscopists were blinded to group allocation. Digital images were taken at 4 locations (lower esophagus/upper gastric body/antrum/fundus), and rated for mucosal visibility (MV) using a 4-point scale (1 = best, 4 = worst) by 4 separate experienced endoscopists. The primary outcome measure was mean mucosal visibility score (MVS). Secondary outcome measures were procedure duration and volume of fluid flush required to achieve adequate mucosal views.Results: Mean MVS for Group A was significantly better than for Group B (1.35 vs 2.11, P < 0.001) and Group C (1.35 vs 2.21, P < 0.001).Mean flush volume required to achieve adequate mucosal views was significantly lower in Group A than Group B (2.0 mL vs 31.5 mL, P = 0.001) and Group C (2.0 mL vs 39.2 mL P < 0.001). Procedure duration did not differ significantly between any of the 3 groups.MV scores at each of the 4 locations demonstrated significantly better mucosal visibility in Group A compared to Group B and Group C (P < 0.0025 for all comparisons). Conclusions: A pre-procedure drink containing simethicone and NAC significantly improves mucosal visibility during gastroscopy and reduces the need for flushes during the procedure. Effectiveness in the lower esophagus demonstrates potential benefit in Barrett’s oesophagus surveillance gastroscopy.